Inhibiting ROS-NF-κB-dependent autophagy enhanced brazilin-induced apoptosis in head and neck squamous cell carcinoma. (March 2017) - He, Zhi-Jing; Zhu, Fei-Ya; Li, Shi-Sheng; Zhong, Liang; Tan, Hong-Yu; Wang, Kai
Abstract: Autophagy modulation has been considered a potential therapeutic strategy for head and neck squamous cell carcinoma (HNSCC). A previous study confirmed that brazilin might possess significant anti-carcinogenic activity. However, whether brazilin induces autophagy and its roles in cell death in HNSCC are still unclear. In this study, we have shown that brazilin induced significant apoptosis in the Cal27 HNSCC cell line but not in oral keratinocyte cell line (OKC). In addition to showing apoptosis induction, we demonstrated the brazilin-induced autophagic response in the Cal27 cells, as evidenced by the formation of GFP-LC3 puncta, and also showed the upregulation of LC3-II and Beclin-1. Moreover, pharmacologically or genetically blocking autophagy enhanced the brazilin-induced apoptosis, indicating the cytoprotective role of autophagy in brazilin-treated Cal27 cells. Moreover, brazilin activated nuclear factor kappa B (NF-κB p65) nuclear translocation and increased NF-κB p65 reporter activity, which contributed to the upregulation of autophagy-related genes, including LC3-II and Beclin-1. Importantly, we found that brazilin triggered reactive oxygen species (ROS) generation in Cal27 cells. Furthermore, N-acetyl-cysteine (NAC), a ROS scavenger, abrogated the effects of brazilin on the NF-κB p65-dependent autophagy. Taken together, our results demonstrated that brazilin increased the NF-κB p65-dependent autophagy through the promotion of ROS signalling pathways in HNSCC. These data also suggest that a strategy of blocking ROS-NF-κB p65-dependent autophagy to enhance the activity of brazilin warrants further attention for the treatment of HNSCC. Highlights: Brazilin-induced apoptosis and autophagy in HNSCC. Brazilin increased the NF-κB p65-dependent autophagy through the promotion of ROS signalling pathways in HNSCC. Blocking ROS-NF-κB p65-dependent autophagy enhanced the activity of brazilin for the treatment of HNSCC.